Pengaruh Kreativitas, Lingkungan Keluarga dan Jiwa Entrepreneur Terhadap Niat Berwirausaha Mahasiswa Stkip Pgri Tulungagung - Muhammad Irwansyah; Hari Subiyantoro (Universitas Hamzanwadi, 2018)
This study aims to determine the influence of creativity, family environment and entrepreneurial spirit to the intention of entrepreneurship of students in the sixth semester of economic education in stkip pgri tulungagung.Populasi research semester VI students as many as 89 students, data collection methods using questionnaires, data analysis using multiple linear regression formula.Results analysis of data Test t tuktilai value t arithmetic (2.167) creativity variable (X1). The variable of the family environment (X2) has a count value (2,426). The entrepreneur (X3) entity variables have a tcount value (2.049.Can concluded partially that